2015
DOI: 10.1007/s12031-015-0533-6
|View full text |Cite
|
Sign up to set email alerts
|

CI-988 Inhibits EGFR Transactivation and Proliferation Caused by Addition of CCK/Gastrin to Lung Cancer Cells

Abstract: Cholecystokinin (CCK) receptors are G-protein coupled receptors (GPCR) which are present on lung cancer cells. CCK-8 stimulates the proliferation of lung cancer cells, whereas the CCK2R receptor antagonist CI-988 inhibits proliferation. GPCR for some gastrointestinal hormones/neurotransmitters mediate lung cancer growth by causing epidermal growth factor (EGF)R transactivation. Here, the role of CCK/gastrin and CI-988 on EGFR transactivation and lung cancer proliferation were investigated. Addition of CCK-8 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The EGFR activates the Ras, Raf, MEK and ERK pathway resulting in altered cellular proliferation. The increase in EGFR and ERK tyrosine phosphorylation caused by addition of CCK-8 to lung carcinoid NCI-H727 cells was significantly inhibited by CI-988, PP2, gefitinib and GM6001, a MMP inhibitor 93 . In gastric epithelial cells, gastrin increases MMP9 expression 94 .…”
Section: Cck Receptors and Other Cancersmentioning
confidence: 94%
“…The EGFR activates the Ras, Raf, MEK and ERK pathway resulting in altered cellular proliferation. The increase in EGFR and ERK tyrosine phosphorylation caused by addition of CCK-8 to lung carcinoid NCI-H727 cells was significantly inhibited by CI-988, PP2, gefitinib and GM6001, a MMP inhibitor 93 . In gastric epithelial cells, gastrin increases MMP9 expression 94 .…”
Section: Cck Receptors and Other Cancersmentioning
confidence: 94%
“…Lung cancer is associated with overexpression of CCK 2 receptors. 34 NCI-H322 was derived in 1981 from a primary bronchioalveolar carcinoma of the lung from a 52 year old male. Cells of this non-small cell carcinoma cell line produce tumours in athymic mice.…”
Section: Cell Based In Vitro Assaymentioning
confidence: 99%
“…Cancer cells produce and secrete the neuropeptides CCK/gastrin [ 34 , 129 ], GRP and NMB [ 130 , 131 ], bradykinin [ 132 ], and vasopressin [ 133 , 134 ]. A plethora of evidence exists elucidating the autocrine growth and pro-proliferative effects exerted by CCK/gastrin [ 135 , 136 ], GRP and NMB [ 137 , 138 ], bradykinin [ 139 , 140 ] and vasopressin [ 21 , 94 , 95 , 141 , 142 ] through their respective receptors. In the process, they increase the colony number of cancer cells, including lung cancer [ 21 , 135 , 143 ].…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of evidence exists elucidating the autocrine growth and pro-proliferative effects exerted by CCK/gastrin [ 135 , 136 ], GRP and NMB [ 137 , 138 ], bradykinin [ 139 , 140 ] and vasopressin [ 21 , 94 , 95 , 141 , 142 ] through their respective receptors. In the process, they increase the colony number of cancer cells, including lung cancer [ 21 , 135 , 143 ]. Weber et al reported that even activation of orphan receptor BRS-3 may contribute to cancer cell proliferation, since the analogue [d-Phe 6 , β-Ala 11 , Phe 13 , Nle 14 ] bombesin (6–14) caused enhanced nuclear oncogene expression, MAPK phosphorylation, and Elk-1 activation in lung cancer cells [ 144 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation